Comparative Analysis of Acyclovir Esters Stability in Solutions: The Influence of the Substituent Structure, Kinetics, and Steric Effects. Issue 11 (22nd September 2015) - Lesniewska, Monika A.; Gola, Michał; Dutkiewicz, Zbigniew; Muszalska, Izabela
ABSTRACT Reversed‐phase high‐performance liquid chromatography has been applied to the determination of acyclovir (ACV) esters such as acetate, isobutyrate, pivalate, ethoxycarbonate, and nicotinate. All analyses were carried out at laboratory temperature using a column LiChrospher RP‐18 (250 × 4 mm, 5 µm) and a proper mobile phase consisting of acetonitrile and phosphate buffer (pH 6 or 6.7) or acetonitrile and potassium dihydrogen phosphate, and acetic acid. The methods were validated by the determination of the following parameters: selectivity, precision, accuracy, and linearity. Kinetic studies on the hydrolysis were investigated in solutions at 310 K over the pH range 0.42–1.38. The pH‐profiles indicated specific acid‐catalyzed and spontaneous water‐catalyzed degradation. The stability of the studied ACV esters were determined not only by steric factors. In the case of ethoxycarbonyl ester of ACV, the hydrolysis was a two‐step reaction.